Exploring Factors Link to Teachers’ Competencies in Entrepreneurship Education - Huang, Yangjie; An, Lanyijie; Liu, Lanying; Zhuo, Zelin; Wang, Peng (Frontiers in Psychology, 2020)
To improve the quality of entrepreneurship education, this study explored factors linked to teachers’ competencies in entrepreneurship education in China. A regression analysis based on 12,596 teachers’ questionnaires showed that the competencies of teachers in entrepreneurship education had three dimensions. The factors linked to teacher’s competencies were professional training, new modes of teaching, entrepreneurial practice, entrepreneurial culture, and policy guarantee. At the same time, the influence mechanism between teachers’ overall competency and factors is explored. For a higher quality of entrepreneurship education, it is necessary to adopt new modes of teaching, pay attention to teachers’ careers, and improve the evaluation and recruitment mechanism for teachers. Our findings provide novel insights by exploring factors linked to teachers’ competencies, extending understanding on improving the quality of entrepreneurship education, and enriching the entrepreneurship education literature by adding new empirical evidence from China.